A study of the effects of claim experience on Texas contractors' routine record keeping - Camp, Gerald Miller, 1951- ([publisher not identified], 1986)
A survey of contractor record keeping is developed and presented. Existing suggested requirements are reviewed. Two hypotheses are tested involving twenty six dependent variables on records kept by contractors. The first hypothesis deals with patterns of routine record keeping as affected by the independent variable of prior claim experience. The second hypothesis deals with expected value in a future claim situation of twenty six dependent variables in regard to the independent variable of prior claim experience. Conclusions are drawn and suggestions are made for further research.